DEVELOPING STUDENTS’ SOCIAL SKILL THROUGH MULTICULTURAL BASED HISTORY LEARNING - Sumantri, Yeni Kurniawati (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2010)
The paper is based on the research on difficulties in history learning particularly in developing the students’ skill. History as one of the national school subjects can be utilized as a medium in developing students’ social skill in order to cope with the complex society. The method can be conducted through multicultural based history learning.The formulation of the research is based on the following questions; why do teachers should apply the multicultural learning system? How to develop a lesson plan and its learning implementation?, how to develop an evaluation on multicultural based history learning?, moreover ,does the multicultural based learning method able to upgrade students’ social skill?.Qualitative research is applied as the research paradigm and action research method is conducted as the tools of analysis. The subject of the study is the 11th grade students of SMA negeri 3 Bandung. The results of the study point out that firstly, the composing of multicultural based lesson plan is applied on the objective formulation, material arrangement, learning method development, and development of learning evaluation. Secondly, the implementation of multicultural based history learning can be elaborated by various learning strategies, particularly strategies involving students’ activity. Thirdly, the learning evaluation on multicultural based history learning shows a positive progress on students’ activity and teachers’ performance. Finally, the well designed multicultural based learning system extends a positive impact on students’ social skill.